2005
DOI: 10.1111/j.1365-2249.2005.02981.x
|View full text |Cite
|
Sign up to set email alerts
|

The time course of biological and immunochemical allergy states induced by anisakis simplex larvae in rats

Abstract: SummaryOral infection by Anisakis simplex third stage larvae (L3) frequently gives rise to an allergic response. To comprehend the allergic and immune responses induced by L3, we investigated the kinetics of specific antibody isotype expression and the time course of biological and immunochemical allergy states using sera prepared from rats orally infected with L3 twice, with an interval of 9 weeks between infections. Biological and immunochemical allergy states were analysed by RBL-2H3 exocytosis and by indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…1B). The kinetics of specific antibodies observed in this study during 1-4 weeks after live L3 inoculation was almost identical to that of the previous study using rats inoculated with 20 live L3 (Cho et al 2005). In contrast, the absorbance values of specific antibodies in rats inoculated with dead L3 were lower than those of the cut-off values during the experimental periods, irrespective of the methods used for inactivating L3 (Fig.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…1B). The kinetics of specific antibodies observed in this study during 1-4 weeks after live L3 inoculation was almost identical to that of the previous study using rats inoculated with 20 live L3 (Cho et al 2005). In contrast, the absorbance values of specific antibodies in rats inoculated with dead L3 were lower than those of the cut-off values during the experimental periods, irrespective of the methods used for inactivating L3 (Fig.…”
supporting
confidence: 56%
“…Therefore, the risk of Anisakis-associated allergic reaction by ingestion of properly cooked and frozen fish remains controversial (Daschner et al 2012;Pravettoni et al 2012). Oral inoculation of rats with live L3 is known to be a useful experimental model for analyse of allergic responses in anisakiasis (Cho et al 2005). To date, seven A. simplex excretory-secretory (ES) allergens that were found to be thermostable or resistant to pepsin digestion have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Cho et al described the specific antibody response in rats that were infected orally with L3 on two occasions at intervals of 9 weeks. The results suggested that the allergic response was elicited by the reinfection (peaking after 1 week) and was accompanied by an elevated IgM level (53). Iglesias and colleagues (117) found some antigens captured by monoclonal antibodies (MAbs) that contain epitopes recognized by human IgE antibodies.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…It has been demonstrated experimentally that rats infected by a single parasite develop higher IgE levels than do rats infected with a high number. Differences have been described between infection and antigen exposure to A. simplex in the sense that reinfection induces a strong Th2 response, whereas antigens alone do so to a lesser degree or not at all (53). In contrast, it has been shown recently that both live parasites and crude extracts of L3 cause allergic reaction in sensitized mice challenged orally with A. simplex proteins, resulting in a striking allergic reaction within as little as 1 hour, accompanied by scratching, irritability, diarrhea, and puffiness around the eyes (237).…”
Section: Innate Immune Responsesmentioning
confidence: 99%